2019
DOI: 10.1101/796466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights from a survey-based analysis of the academic job market

Abstract: Many postdoctoral fellows in the STEM fields enter the academic job market with little knowledge of the process and expectations, and without any means to assess their qualifications relative to the general applicant pool. Demystifying this process is critical, as there is little information publicly available. In this work, we provide insight into the process of academic job searches by gathering data to establish background metrics for typical faculty job applicants, and further correlate these metrics with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The rise in the number of social science postdocs, as in other fields, can be attributed to factors such as shifts in funding mechanisms for academic research (Britt, 2012; Foley, 2013); the increasingly adverse job market conditions for tenure-track faculty positions (American Association of University Professors, 2018; Cantwell and Taylor, 2015; Fernandes et al , 2019; Kezar and Sam, 2010; Neumann and Tan, 2011; Stephan and Ma, 2005); and growing enrollment in graduate degree programs (Arbeit and Kang, 2017; Einaudi et al , 2013). The proportion of PhDs who take postdoc positions also tends to vary due to economic conditions.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…The rise in the number of social science postdocs, as in other fields, can be attributed to factors such as shifts in funding mechanisms for academic research (Britt, 2012; Foley, 2013); the increasingly adverse job market conditions for tenure-track faculty positions (American Association of University Professors, 2018; Cantwell and Taylor, 2015; Fernandes et al , 2019; Kezar and Sam, 2010; Neumann and Tan, 2011; Stephan and Ma, 2005); and growing enrollment in graduate degree programs (Arbeit and Kang, 2017; Einaudi et al , 2013). The proportion of PhDs who take postdoc positions also tends to vary due to economic conditions.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…Despite remarkable progress made over the last three decades to mitigate gender bias (Eagly, 2018), equity is still far from being reached in academia. Multiple studies have systematically documented bias in every aspect of academia (Fernandes et al, 2020), including journal article and innovation citations (Dworkin et al, 2020b;Hofstra et al, 2020), publication rates (West et al, 2013), patent applications (Jensen et al, 2018), hiring decisions (Nielsen, 2016), research grant applications (Burns et al, 2019), evaluations of conference abstracts (Knobloch-Westerwick et al, 2013), symposia speaker invitations (Schroeder et al, 2013), postdoctoral employment (Sheltzer and Smith, 2014), prestigious science awards (Lunnemann et al, 2019), and tenure decisions (Weisshaar, 2017). These forms of bias are intertwined and evolve and accumulate along the career path (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the gender of these gate-keepers affects the gender ratio of other authors on a paper is unknown, but perhaps vital to understand gender imbalances in academia. For example, a recent survey found that STEM postdoctoral fellows entering the academic job market had an average of 13 publications, six of them first-authored (Fernandes et al 2019). Therefore, publications on which a researcher is a collaborator, but not the research lead, may represent more than half of that early career researcher's publications.…”
Section: Introductionmentioning
confidence: 99%